Moment inequalities and their application - A. Pakes; J. Porter; Kate Ho; Joy Ishii (Centre for Microdata Methods and Practice (cemmap), 2007)
This paper provides conditions under which the inequality constraints generated by either single agent optimizing behavior, or by the Nash equilibria of multiple agent problems, can be used as a basis for estimation and inference. We also add to the econometric literature on inference in models defined by inequality constraints by providing a new specification test and methods of inference for the boundaries of the model's identified set. Two applications illustrate how the use of inequality constraints can simplify the problem of obtaining estimators from complex behavioral models of substantial applied interest.
Keywords: 330; Schätztheorie; Momentenmethode; Theorie